Bridging the Financing Gap in Halal Tourism Infrastructure: A Legal and Economic Reconstruction of Cash Waqf Linked Deposit (CWLD) - Imam Kamaluddin; Ahmad Zaki Al Fanani; Mushaq Syamsuar; Abdul Nafi' Nur Fauzan; Irawan Irawan (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2026)
The global halal tourism industry serves as a strategic pillar that substantially contributes to Indonesia's Gross Domestic Product. Nevertheless, its development remains impeded by fundamental constraints, particularly a significant financing gap in infrastructure provision. This study aims to conceptually reconstruct the Cash Waqf Linked Deposit (CWLD) instrument to serve as an alternative legal and Islamic economic framework for financing macro-scale halal tourism infrastructure. Employing a qualitative library research approach, this study evaluates data sourced from academic journals, scholarly literature, and regulations of the Financial Services Authority through thematic analysis. The findings propose a multi-contract scheme encompassing Wadi'ah or Mudharabah Mutlaqah during the fund accumulation phase, Mudharabah Muqayyadah for project investment disbursement, and Wakalah bil Ujrah for the Nazhir. This model ensures the preservation of the waqf principal while facilitating highly cost-effective funding for developers. Furthermore, the investment yields are allocated to subsidize halal certification for local Micro, Small, and Medium Enterprises (MSMEs), thereby fostering an integrated and sustainable socio-economic ecosystem within the halal value chain. As a conceptual study, this proposed model has yet to undergo empirical validation. However, the study suggests that CWLD has the potential to serve as an alternative Islamic social finance instrument for supporting halal tourism infrastructure, provided that regulatory safeguards, professional nazhir governance, and project risk mitigation mechanisms are properly established. Future empirical validation utilizing Interpretive Structural Modeling (ISM) or Analytic Network Process (ANP) methodologies is highly recommended to operationalize this framework.